Genomic Clues for Crop–Weed Interactions and Evolution. (December 2018) - Guo, Longbiao; Qiu, Jie; Li, Lin-Feng; Lu, Baorong; Olsen, Kenneth; Fan, Longjiang
Abstract : Agronomically critical weeds that have evolved alongside crop species are characterized by rapid adaptation and invasiveness, which can result in an enormous reduction in annual crop yield worldwide. We discuss here recent genome-based research studies on agricultural weeds and crop–weed interactions that reveal several major evolutionary innovations such as de-domestication, interactions mediated by allelochemical secondary metabolites, and parasitic genetic elements that play crucial roles in enhancing weed invasiveness in agricultural settings. We believe that these key studies will guide future research into the evolution of crop–weed interactions, and further the development of practical applications in agricultural weed control and crop breeding. Highlights: Agricultural weeds can be generally classified into weedy crop relatives and non-crop relatives based on their genetic relationship to crops. They are not only economically important but are fascinating models for studying the adaptation and rapid evolution of plant species in human-mediated environments. Allelopathy by secondary metabolites is a central process underlying crop–weed interactions in agroecosystems. Biosynthetic gene clusters may be one important genomic mechanism governing these allelopathic interactions. Genetic exchanges occur frequently between crops and parasitic weeds, and can evidently have functional consequences. Recent genomic studies of weedy plants are providing in-depth insights into the evolution of weeds and the mechanisms of crop–weed interactions, and are likely to have a major impact on weed management and crop breeding.